Preparation method of high-temperature-resistant flame-retardant nano calcium carbonate with good dispersibility

By introducing the carboborane cage structure and the phosphate group containing benzene ring in the process of nano calcium carbonate synthesis, the problem of limited application of nano calcium carbonate in high temperature and flame retardant fields is solved, and the material's high temperature resistance and flame retardant properties are achieved significantly improved.

CN119708627APending Publication Date: 2025-03-28HUBEI THREE GORGES LAB +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411763049.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The application of nano calcium carbonate in high temperature and flame retardant fields is limited, because it has poor thermal stability, poor dispersion, and does not have high high temperature resistance and flame retardant properties in organic media.

Method used

By introducing a carboboane cage structure and a phosphate group containing a benzene ring in the nano calcium carbonate synthesis process, the B atoms and calcium ions are used to form coordination bonds, promote the directional growth of grains, reduce surface energy, and improve the high temperature resistance and flame retardant properties of the material through the thermal stabilization of the phosphate groups.

Benefits of technology

It significantly improves the high temperature resistance and flame retardant properties of nano calcium carbonate, enhances its dispersion in organic media, and is suitable for application scenarios with high temperature and flame retardant requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708627A_ABST
    Figure CN119708627A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of high-temperature-resistant flame-retardant nano calcium carbonate with good dispersibility. Adding the calcium hydroxide slurry into a carbonization reaction kettle, adding a first crystal form control agent, introducing CO2 gas, starting stirring, adding a second crystal form control agent after a gel phenomenon occurs, continuously reacting until the conductivity is reduced to the lowest point, and ending the reaction; heating the slurry to 60-90 DEG C, starting stirring, and carrying out aging reaction under a heat preservation condition; and after the aging reaction is finished, adding a compound surface modifier to carry out activation reaction, and then carrying out suction filtration, washing and drying to prepare the high-temperature-resistant flame-retardant nano calcium carbonate with good dispersibility. The cubic nano calcium carbonate particles with good dispersibility are successfully prepared by introducing the crystal form control agent with a carborane structure and using the sodium stearate and the surface modifier compounded by the phosphate ester / phosphate sodium salt containing a benzene ring structure, so that the high-temperature resistance of the nano calcium carbonate is improved, and meanwhile, the nano calcium carbonate particles have high dispersibility; the heat and humidity resistance and the flame retardant property are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention discloses a method for preparing nano calcium carbonate with high temperature resistance, flame retardancy and good dispersibility. Background Art

[0002] Nano calcium carbonate is a functional inorganic filler, non-toxic and harmless, with an average particle size of about 30-100 nm. The changes in its crystal structure and surface electronic structure give it surface effects, small size effects, macroscopic quantum tunneling effects, etc. that ordinary calcium carbonate does not have, so it has unique properties in optics, thermal, electrical, mechanical and chemical aspects, including high specific surface area, excellent reinforcement performance, thickening effect and anti-settling performance, etc. These advantages make it widely used in many fields such as plastics, rubber, papermaking, coatings, inks, lubricants, concrete, food, medicine, ceramics, lithium batteries and environmental protection, and become a key material to improve product performance.

[0003] At present, the market of nano-calcium carbonate is highly competitive. Foreign enterprises such as MTI, ICI, Solvay, Shiraishi and Maruo Calcium, etc., with strong R&D and innovation capabilities, have continuously launched nano-calcium carbonate products with excellent performance, occupying most of the domestic high-end market. Domestic enterprises such as Lanhua Nano, Wufeng Materials, Kailong Co., Ltd., Shandong Shengda Technology, etc., have gradually gained a certain position and influence in the domestic market by continuously improving their R&D capabilities, optimizing production processes and improving product quality. However, compared with foreign enterprises, although the preparation technology of nano-calcium carbonate is relatively mature, there are still some technical bottlenecks, such as particle size control, shape regulation, unstable product quality, large surface energy and easy agglomeration, and the hydrophilic and oleophobic surface characteristics lead to poor dispersibility in organic media, poor compatibility with base materials, etc., which cause defects and reduce the performance of downstream products, affecting the market competitiveness and application effect of products.

[0004] The common nano calcium carbonate on the market generally has an initial decomposition temperature of around 300°C, and a large amount of decomposition occurs above 400°C. However, in actual applications, downstream application products of nano calcium, such as silicone structural adhesive, will begin to show yellowing, curling, bubbles and micro cracks when heated at 160°C for two hours. Analysis shows that this is because the organic modifier coated on the surface of nano calcium has poor thermal stability and a low decomposition temperature, which leads to a decline in product quality. Therefore, it is necessary to explore the preparation of a high temperature resistant, highly dispersible nano calcium carbonate product to meet market demand.

[0005] Carborane is an icosahedral cage structure, whose vertices are replaced by one or more carbon atoms. Due to the different number and position of substitution, a series of carborane derivatives are formed. The electron-deficient nature of the boron atom causes its electron cloud to be in a highly delocalized state, thus showing superaromaticity and good physical and chemical stability. Therefore, the introduction of carborane structural units into the compound structure can not only enhance rigidity and improve the high temperature resistance of the polymer, but also have a flame retardant effect.

[0006] Flame retardant materials are materials that can slow down the spread of fire. Their main components include phosphorus, nitrogen, silicon and other elements. Among them, phosphorus is one of the most common components in flame retardant materials. Its main function is to slow down the spread of fire by absorbing heat. Nitrogen is another common component. It can lower the ignition point of the material, thereby slowing down the ignition speed. Silicon can form a protective layer to slow down the heat release when the material burns. In addition to the above main components, flame retardant materials may also contain other elements, such as oxygen, fluorine and some rigid ring structures. They mainly increase the heat resistance and oxidation resistance of the material, thereby improving the flame retardant effect.

[0007] Nano calcium carbonate has limited applications in the fields of high temperature resistance and flame retardancy due to its poor thermal stability, and there are few related reports. Therefore, further improving its high temperature resistance, flame retardancy and high dispersibility in organic media are technical problems that researchers in this field need to solve. Summary of the invention

[0008] In order to solve the above problems, the present invention proposes a method for preparing nano calcium carbonate with good high temperature resistance, flame retardancy and dispersibility, which is characterized by comprising the following steps: S1: Add calcium hydroxide slurry into the carbonization reactor, add the first crystal form control agent, and pass CO 2 Gas, start stirring, after gelation occurs, add the second crystal form control agent, and continue the reaction until the conductivity drops to the lowest point, marking the end of the reaction; S2: Raise the temperature of the carbonized slurry to 60-90°C, start low-speed stirring, and perform aging reaction under heat preservation conditions; S3: After the aging reaction is completed, a compounded surface modifier is added to the reactor for activation reaction, followed by suction filtration, washing, and drying to obtain nano calcium carbonate with good high temperature resistance, flame retardancy, and dispersibility.

[0009] Preferably, the concentration of the calcium hydroxide slurry in step S1 is in the range of 8% to 12%, and the initial carbonization temperature is 15 to 35°C.

[0010] Preferably, the CO in step S1 2 The concentration is 30~40%.

[0011] The first crystal form controlling agent in step S1 is at least one or a combination of sugars and organic acids, wherein the sugars include sucrose and glucose; and the organic acids include sebacic acid, octanoic acid, cinnamic acid, hexadecanoic acid, 6-phenylhexanoic acid, octyl phosphoric acid and perfluorononanoic acid.

[0012] The second crystal form controlling agent described in step S1 is at least one of carborane derivatives, including o-carborane bisphenol, m-carborane bisphenol, 1-carboxyl o-carborane, 1,7-dicarboxylic acid m-carborane, etc.

[0013] When the first crystal form controlling agent described in step S1 is only sugar, the added amount is 1-5% of the dry mass of calcium hydroxide.

[0014] When the first crystal form controlling agent described in step S1 is only an organic acid, the added amount is 2-6% of the dry basis mass of calcium hydroxide.

[0015] The first crystal form controlling agent described in step S1 is sugar and organic acid, and the total addition amount is 3-7% of the dry basis mass of calcium hydroxide.

[0016] The second crystal form controlling agent described in step S1 is a carborane derivative, and the added amount is 0.1-1% of the dry mass of calcium hydroxide.

[0017] The aging reaction time in step S2 is 4-12 hours.

[0018] The aging reaction CO in step S2 2 There are two aeration methods: aeration after completion or continuous aeration during the aging process. The reaction ends when pH < 7.5.

[0019] The compounding of the surface modifier in step S2 comprises compounding sodium stearate and at least one of a phosphate ester or a phosphate containing a benzene ring structure, comprising the following steps: (1): Add the prepared sodium stearate saponified solution into the reactor, recorded as emulsion A; (2): Add the prepared phosphate ester or phosphate solution into the reactor and stir to obtain emulsion B, which is the compound surface modifier.

[0020] Preferably, the mass ratio of stearic acid / sodium hydroxide / water in emulsion A is 1:6-10:5-10 for reaction to obtain sodium stearate saponified liquid; Preferably, the stearic acid content in emulsion A is 1-5% of the dry mass of calcium carbonate; Preferably, emulsion B comprises at least one of phosphate esters or phosphate salts containing a benzene ring structure.

[0021] Preferably, the phosphate ester containing benzene ring structure in emulsion B includes 4-methylumbelliferyl phosphate, S-binaphthol phosphate, R-binaphthol phosphate, 1-naphthyl phosphate, 2-naphthyl phosphate and bis(2,4-di-tert-butylphenyl) phosphate.

[0022] Preferably, the sodium phosphate salt containing a benzene ring structure in emulsion B includes 4-methylumbelliferyl phosphate disodium salt, 1-naphthyl phosphate disodium salt and 2-naphthyl phosphate monosodium salt.

[0023] Preferably, the phosphate content in emulsion B is 1-5% of the dry weight of calcium carbonate, and the phosphate content is 0.1-2% of the dry weight of calcium carbonate.

[0024] A nano calcium carbonate with high temperature resistance, flame retardancy and high dispersibility comprises the nano calcium carbonate obtained by the above-mentioned preparation method.

[0025] An application of the aforementioned nano calcium carbonate with high temperature resistance, flame retardancy and high dispersibility is characterized in that it is used as a filler in plastics, rubbers, coatings, sealants and other products with high temperature resistance and flame retardancy to reduce costs and increase efficiency.

[0026] Compared with the prior art, the present invention has the following beneficial effects: The present invention introduces a carborane cage structure in the synthesis process of nano calcium carbonate through molecular structure design, wherein the lone pair of electrons contained in the B atom forms a coordination bond with the calcium ion, so that the grains grow in a directional manner, particle agglomeration is reduced, and surface energy is lowered, thereby improving the dispersibility of the nano calcium carbonate.

[0027] The invention introduces a carborane cage structure in the synthesis process of nano calcium carbonate through molecular structure design, and introduces a phosphate group containing a benzene ring into a surface modifier. The introduction of these rigid structures, together with the thermal stabilization effect of the phosphate group and the high melting point of stearic acid metal soap, is more conducive to improving the high temperature resistance and wet heat resistance of the nano calcium carbonate.

[0028] The nano calcium carbonate of the present invention contains two elements, B and P. The boron element can be oxidized at high temperature to form a protective layer of boron oxide to isolate the propagation of oxygen and heat and inhibit the generation of thick smoke. The P element can slow down the spread of fire by absorbing heat. Therefore, the nano calcium carbonate is used as a filler in downstream products such as sealants, plastics, and oil paper. The synergistic effect of the two elements B and P can promote the improvement of the flame retardant performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 (a) is a TEM image of nano-calcium carbonate particles in implementation case 8 at a magnification of 50 nm, and (b) is a TEM image of nano-calcium carbonate particles in comparison case 1 at a magnification of 50 nm.

[0030] Figure 2This is a comparison chart of the thermogravimetric curves of the nano calcium carbonate prepared in Example 8 and the conventional nano calcium (Lanhua SP200) sold on the market. DETAILED DESCRIPTION

[0031] The present invention will be described in more detail below. The present invention can be implemented in many forms and is not limited to the implementation examples described herein.

[0032] Example 1 S1: Add 12% calcium hydroxide slurry into the carbonization reactor, add 4% sucrose based on the dry weight of calcium hydroxide, the initial carbonization temperature is 20°C, CO 2 The concentration is 30%. After the gelation phenomenon occurs, 0.3% of m-carborane bisphenol on a dry basis of calcium hydroxide is added until the conductivity of the reaction system drops to the lowest point, and the carbonization reaction is completed.

[0033] S2: The carbonized slurry is heated to 60°C and kept warm for 4 hours. After the aging, secondary carbonization is performed. 2 The reaction ends when the concentration is 30% and pH < 7.5.

[0034] S3: Under the condition of 60°C insulation, 3% sodium stearate saponification liquid and 2% surface modifier of bis(2,4-di-tert-butylphenyl) phosphate compound are added into the reactor for activation reaction. After the reaction, the reaction is filtered, washed and dried to obtain the nano calcium carbonate with good high temperature resistance, flame retardancy and dispersibility.

[0035] Example 2 S1: Add 12% calcium hydroxide slurry into the carbonization reactor, add 3% sucrose and 2% cinnamic acid based on the dry weight of calcium hydroxide. The initial carbonization temperature is 20℃, CO 2 The concentration is 30%. After the gelation phenomenon occurs, 0.3% of m-carborane bisphenol on a dry basis of calcium hydroxide is added until the conductivity of the reaction system drops to the lowest point, and the carbonization reaction is completed.

[0036] S2: The carbonized slurry is heated to 70°C and kept warm for 4 hours. After the aging, a secondary carbonization is performed. 2 The reaction ends when the concentration is 30% and pH < 7.5.

[0037] S3: Under the condition of 70°C insulation, 3% of sodium stearate saponified liquid and 2% of a surface modifier of bis(2,4-di-tert-butylphenyl) phosphate were added to the reactor for activation reaction. After the reaction, the mixture was filtered, washed and dried to obtain the nano calcium carbonate with good high temperature resistance, flame retardancy and dispersibility.

[0038] Example 3 S1: Add 12% calcium hydroxide slurry into the carbonization reactor, add 3% sucrose and 2% octyl phosphoric acid based on the dry weight of calcium hydroxide. The initial carbonization temperature is 20℃, CO 2 The concentration is 30%. After the gelation phenomenon occurs, 0.3% of m-carborane bisphenol on a dry basis of calcium hydroxide is added until the conductivity of the reaction system drops to the lowest point, and the carbonization reaction is completed.

[0039] S2: The carbonized slurry is heated to 70°C and kept warm for 4 hours. After the aging, a secondary carbonization is performed. 2 The reaction ends when the concentration is 30% and pH < 7.5.

[0040] S3: Under the condition of 70°C insulation, 3% of sodium stearate saponified liquid and 2% of a surface modifier of bis(2,4-di-tert-butylphenyl) phosphate were added to the reactor for activation reaction. After the reaction, the mixture was filtered, washed and dried to obtain the nano calcium carbonate with good high temperature resistance, flame retardancy and dispersibility.

[0041] Example 4 S1: Add 12% calcium hydroxide slurry into the carbonization reactor, add 3% sucrose and 2% 6-phenylhexanoic acid based on the dry weight of calcium hydroxide. The initial carbonization temperature is 25°C, CO 2 The concentration is 30%. After the gelation phenomenon occurs, 0.3% of m-carborane bisphenol on a dry basis of calcium hydroxide is added until the conductivity of the reaction system drops to the lowest point, and the carbonization reaction is completed.

[0042] S2: The carbonized slurry is heated to 70°C and kept warm for 4 hours. After the aging, a secondary carbonization is performed. 2 The reaction ends when the concentration is 30% and pH < 7.5.

[0043] S3: Under the condition of 70°C insulation, 3% of sodium stearate saponified liquid and 2% of a surface modifier of bis(2,4-di-tert-butylphenyl) phosphate were added to the reactor for activation reaction. After the reaction, the mixture was filtered, washed and dried to obtain the nano calcium carbonate with good high temperature resistance, flame retardancy and dispersibility.

[0044] Example 5 S1: Add 12% calcium hydroxide slurry into the carbonization reactor, add 3% sucrose and 2% 6-phenylhexanoic acid based on the dry weight of calcium hydroxide. The initial carbonization temperature is 25°C, CO 2 The concentration is 30%. After the gelation phenomenon occurs, 0.3% of 1-carboxyl o-carborane by dry weight of calcium hydroxide is added until the conductivity of the reaction system drops to the lowest point, and the carbonization reaction is completed.

[0045] S2: The carbonized slurry is heated to 80°C and kept warm for 4 hours. After the aging, secondary carbonization is performed. 2 The reaction ends when the concentration is 30% and pH < 7.5.

[0046] S3: Under the condition of 80°C, a surface modifier prepared by adding 3% sodium stearate saponification solution and 2% 4-methylumbelliferyl phosphate compounded with calcium carbonate dry weight is added into the reactor for activation reaction. After the reaction is completed, the mixture is filtered, washed and dried to obtain the nano calcium carbonate with good high temperature resistance, flame retardancy and dispersibility.

[0047] Example 5 S1: Add 12% calcium hydroxide slurry into the carbonization reactor, add 3% sucrose and 2% 6-phenylhexanoic acid based on the dry weight of calcium hydroxide. The initial carbonization temperature is 25°C, CO 2 The concentration is 30%. After the gelation phenomenon occurs, 0.3% of 1,7-dicarboxylic acid meta-carborane by dry weight of calcium hydroxide is added until the conductivity of the reaction system drops to the lowest point, and the carbonization reaction ends.

[0048] S2: The carbonized slurry is heated to 80°C and kept warm for 4 hours. After the aging, secondary carbonization is performed. 2 The reaction ends when the concentration is 30% and pH < 7.5.

[0049] S3: Under the condition of 80°C, a surface modifier prepared by adding 3% sodium stearate saponification solution and 2% 4-methylumbelliferyl phosphate compounded with calcium carbonate dry weight is added into the reactor for activation reaction. After the reaction is completed, the mixture is filtered, washed and dried to obtain the nano calcium carbonate with good high temperature resistance, flame retardancy and dispersibility.

[0050] Example 6 S1: Add 12% calcium hydroxide slurry into the carbonization reactor, add 3% sucrose and 2% 6-phenylhexanoic acid based on the dry weight of calcium hydroxide. The initial carbonization temperature is 25°C, CO 2 The concentration is 30%. After the gelation phenomenon occurs, 0.5% of 1,7-dicarboxylic acid meta-carborane by dry weight of calcium hydroxide is added until the conductivity of the reaction system drops to the lowest point, and the carbonization reaction ends.

[0051] S2: The carbonized slurry is heated to 80°C and kept warm for 4 hours. After the aging, secondary carbonization is performed. 2 The reaction ends when the concentration is 30% and pH < 7.5.

[0052] S3: Under the condition of 80°C insulation, 3% of sodium stearate saponified solution by dry basis weight of calcium carbonate, 1.5% of 4-methylumbelliferyl phosphate and 0.2% of 1-naphthyl phosphate disodium salt compounded surface modifier are added into the reactor for activation reaction. After the reaction is completed, the mixture is filtered, washed and dried to obtain the nano calcium carbonate with good high temperature resistance, flame retardancy and dispersibility.

[0053] Example 7 S1: Add 12% calcium hydroxide slurry into the carbonization reactor, add 3% sucrose and 2.0% 6-phenylhexanoic acid based on the dry weight of calcium hydroxide. The initial carbonization temperature is 25°C, CO 2 The concentration is 30%. After the gelation phenomenon occurs, 0.5% of 1,7-dicarboxylic acid meta-carborane by dry weight of calcium hydroxide is added until the conductivity of the reaction system drops to the lowest point, and the carbonization reaction ends.

[0054] S2: The carbonized slurry is heated to 80°C and kept warm for 4 hours. After the aging, secondary carbonization is performed. 2 The reaction ends when the concentration is 30% and pH < 7.5.

[0055] S3: Under the condition of 80°C insulation, 3% of sodium stearate saponified solution by dry basis weight of calcium carbonate, 1.5% of 4-methylumbelliferyl phosphate and 0.4% of 2-naphthyl phosphate monosodium salt composite surface modifier are added into the reactor for activation reaction. After the reaction is completed, the mixture is filtered, washed and dried to obtain the nano calcium carbonate with good high temperature resistance, flame retardancy and dispersibility.

[0056] Example 8 S1: Add 12% calcium hydroxide slurry into the carbonization reactor, add 3% sucrose and 2.5% 6-phenylhexanoic acid based on the dry weight of calcium hydroxide. The initial carbonization temperature is 28°C, CO 2 The concentration is 30%. After the gelation phenomenon occurs, 0.5% of 1,7-dicarboxylic acid meta-carborane by dry weight of calcium hydroxide is added until the conductivity of the reaction system drops to the lowest point, and the carbonization reaction ends.

[0057] S2: The carbonized slurry is heated to 90°C and kept warm for 4 hours. After the aging, secondary carbonization is performed. 2 The reaction ends when the concentration is 30% and pH < 7.5.

[0058] S3: Under the condition of 90°C insulation, 3% of sodium stearate saponified solution by dry basis weight of calcium carbonate, 1.5% of 4-methylumbelliferyl phosphate and 0.4% of 4-methylumbelliferyl phosphate disodium salt composite surface modifier are added into the reactor for activation reaction. After the reaction is completed, the mixture is filtered, washed and dried to obtain the nano calcium carbonate with good high temperature resistance, flame retardancy and dispersibility.

[0059] In order to verify that the introduction of carborane cage and phosphate structure containing benzene ring improves the high temperature resistance of nano calcium carbonate, the following two comparative cases were made based on implementation case 8: Comparative Case 1: No carborane cage-type crystal control agent S1: Add 12% calcium hydroxide slurry into the carbonization reactor, add 3% sucrose and 2.5% 6-phenylhexanoic acid based on the dry weight of calcium hydroxide. The initial carbonization temperature is 28°C, CO 2 When the concentration is 30% and the conductivity of the reaction system drops to the lowest point, the carbonization reaction ends.

[0060] S2: The carbonized slurry is heated to 90°C and kept warm for 4 hours. CO is continuously passed during the aging process. 2 The reaction ends when pH < 7.5.

[0061] S3: Under the condition of 90℃, 3% sodium stearate saponification liquid of dry calcium carbonate, 1.5% 4-methylumbelliferyl phosphate and 0.4% 4-methylumbelliferyl phosphate disodium salt composite surface modifier are added into the reactor for activation reaction. After the reaction, the mixture is filtered, washed and dried to obtain nano calcium carbonate.

[0062] Comparative Case 2: Replace the phosphate modifier containing benzene ring structure with a phosphate modifier with a chain structure S1: Add 12% calcium hydroxide slurry into the carbonization reactor, add 3% sucrose and 2.5% 6-phenylhexanoic acid based on the dry weight of calcium hydroxide. The initial carbonization temperature is 28°C, CO 2 The concentration is 30%. After the gelation phenomenon occurs, 0.5% of 1,7-dicarboxylic acid meta-carborane by dry weight of calcium hydroxide is added until the conductivity of the reaction system drops to the lowest point, and the carbonization reaction ends.

[0063] S2: The carbonized slurry is heated to 90°C and kept warm for 4 hours. CO is continuously passed during the aging process. 2 The reaction ends when pH < 7.5.

[0064] S3: Under the condition of 90℃, 3% sodium stearate saponification liquid of dry calcium carbonate and 2% hexadecyl phosphate compound surface modifier are added into the reactor for activation reaction. After the reaction, the mixture is filtered, washed and dried to obtain nano calcium carbonate.

[0065] Table 1 shows the thermal decomposition temperatures (T) corresponding to 5% weight loss in air atmosphere for implementation cases 1 to 8 and comparative cases 1 and 2, respectively. 5%d ) and the moisture content after being placed at 120℃ and 50% humidity for 7 days.

[0066] name <![CDATA[T 5%d ]]> Moisture content name <![CDATA[T 5%d ]]> Moisture content Example 1 560℃ 0.56 Example 6 618℃ 0.34 Example 2 574℃ 0.48 Example 7 625℃ 0.32 Example 3 568℃ 0.50 Example 8 670℃ 0.30 Example 4 580℃ 0.46 Comparative Case 1 580℃ 0.48 Example 5 595℃ 0.40 Comparative Case 2 607℃ 0.38 It is not difficult to find from the experimental data of Examples 1 to 8 in Table 1 that the nano calcium carbonate T prepared according to Example 8 5%d The highest is 670℃, with the best high temperature resistance, and the lowest water absorption rate under long-term hot and humid conditions, only 0.30, with excellent hot and humid resistance.

[0067] Comparing the data of Example 8, Comparative Example 1 and Comparative Example 2 in Table 1, it is found that: without adding nano calcium carbonate T with carborane structure 5%d The lowest temperature is 580℃ (Comparative Case 1), and the nano-calcium carbonate T prepared by replacing the benzene ring-containing phosphate modifier with a chain-structured phosphate modifier 5%d The highest is 607℃ (Comparative Case 2), and the nano calcium carbonate T containing both carborane cage and phosphate structure containing benzene ring 5%d The highest is 670°C (Implementation Case 8). At the same time, the water absorption rate under long-term hot and humid conditions also follows the above rules. The above data confirm that the introduction of the carborane cage structure and the phosphate group containing the benzene ring structure greatly improves the material's high temperature resistance and hot and humid resistance.

[0068] Figure 1 : (a) is a TEM image of the nano calcium carbonate particles prepared in Example 8 at a magnification of 50nm, and (b) is a TEM image of the particles in Comparative Example 1 at a magnification of 50nm. By comparison, it is not difficult to find that the nano calcium carbonate crystals prepared in Example 8 have high overall dispersibility, and the crystals are aggregated in three or four particles instead of the common flake or cluster aggregation. The crystal form is very regular, the morphology is cubic, and the particle size distribution is uniform, which proves that the introduction of the carborane cage structure significantly improves the dispersibility of the nano calcium carbonate.

[0069] Figure 2 The thermogravimetric curves of the nano-calcium carbonate prepared in Example 8, Comparative Example 1 and Comparative Example 2 are compared. The test results show that the nano-calcium carbonate prepared in Example 8 has a Tg of 1.143 W / m2 under air atmosphere. 5%d The temperature of the nano calcium carbonate prepared in Example 1 is 670℃. 5%d The temperature of the nano calcium carbonate prepared in Example 2 is 580℃. 5%d The temperature of the material is 607°C. In comparison, the high temperature resistance of Example 8 is significantly improved, which proves that the addition of the carborane cage structure and the phosphate group containing a benzene ring improves the high temperature resistance of the material.

[0070] Application Cases The nano calcium carbonate with good high temperature resistance, flame retardancy and dispersibility prepared by the present invention is applied to the preparation of silicone building adhesive. The preparation of the silicone building adhesive includes the following steps: Synthesis of base material: Add 30 parts of 107 glue with a molecular weight of 20,000, 50 parts of nano calcium carbonate, 13 parts of heavy calcium, and 7 parts of dimethyl silicone oil into a vacuum kneader, evacuate, heat, stir, raise the temperature to 100°C, and time for 2 hours.

[0071] Synthesis of glue: take a certain amount of base material into a planetary mixer, evacuate the vacuum, and stir; then add ketoxime additive and color paste, evacuate the vacuum, stir, discharge the material, pour the glue into a white bottle, seal it and store it, and prepare for application testing.

[0072] The nano calcium carbonate prepared in implementation cases 1 to 8 and comparative cases 1 and 2 were respectively applied to the preparation of silicone building adhesives, numbered corresponding to application cases 1 to 10, and the mechanical properties, moisture and heat resistance and flame retardant properties were tested. The mechanical properties were tested in accordance with GB / T13477.8, the moisture and heat resistance was tested under the conditions of 120°C and 100% relative humidity for 48 hours, and the flame retardant grade was tested in accordance with GB / T 14683-2017 standard. The test results are shown in Table 2.

[0073] Table 2:

[0074] From the experimental data of Application Examples 1 to 8 in Table 2, it is not difficult to find that the silicone construction adhesive prepared in Application Example 8 has the highest tensile strength of 1.84 MPa and the largest elongation at break. After being placed at 120°C and 100% relative humidity for 48 hours, the mechanical properties were tested, and the retention rates of tensile strength and elongation at break were both around 85%, indicating that the adhesive has excellent high temperature resistance and moisture and heat resistance. In addition, the flame retardant grade is V-0, indicating that it has good flame retardant properties.

[0075] Comparing the experimental data of Application Examples 8 to 10 in Table 2, it is found that Application Example 8 has the highest tensile strength and elongation at break, and the performance retention rate in a hot and humid environment is still the highest, followed by Application Example 9, and Application Example 10 is the lowest. It is also found that compared with Application Example 8, the flame retardant rating of Application Examples 9 and 10 has decreased. Combined with the conclusion drawn from the data in Table 1, it is once again confirmed that the introduction of the carborane cage structure and the phosphate group containing the benzene ring structure significantly improves the high temperature resistance, hot and humid resistance and flame retardant properties of the material.

[0076] In summary, the present invention prepares a nano calcium carbonate with high temperature resistance, flame retardancy and good dispersibility.

[0077] The application of the present invention is not limited to the field of silicone building adhesives, but can also be used as fillers in products in other fields, such as plastics, rubber, coatings and papermaking, to achieve the purpose of reducing costs and increasing efficiency.

[0078] The present invention only illustrates the detailed preparation process of the present invention through the above-mentioned implementation cases, but is not limited to the present invention must rely on the above-mentioned detailed process to be implemented. Any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing nano calcium carbonate with good high temperature resistance, flame retardancy and dispersibility, characterized in that: The following steps are involved: S1: Add calcium hydroxide slurry to the carbonization reactor, add the first crystal form controller, pass CO2 gas, start stirring, and after gelation occurs, add the second crystal form controller and continue the reaction until the conductivity drops to the lowest point, and the reaction is terminated; S2: heating the slurry of step S1 to 60-90°C, starting stirring, and performing aging reaction under heat preservation conditions; S3: After the aging reaction is completed, a composite surface modifier is added to perform an activation reaction, followed by suction filtration, washing, and drying to obtain nano calcium carbonate with good high temperature resistance, flame retardancy, and dispersibility.

2. The method for preparing the nano calcium carbonate with good high temperature resistance and flame retardancy dispersibility according to claim 1, characterized in that: The concentration of the calcium hydroxide slurry in step S1 is in the range of 8% to 12%, the initial temperature of carbonization is 15 to 35°C, the stirring speed is 600 to 2000 r / min; and the CO2 concentration is 30 to 40%.

3. The method for preparing the nano calcium carbonate with good high temperature resistance and flame retardancy dispersibility according to claim 1, characterized in that: The first crystal form controlling agent in step S1 is at least one or a combination of two of sugars and organic acids; wherein the sugars include sucrose and glucose; the organic acids include sebacic acid, cinnamic acid, tridecanoic acid, hexadecanoic acid, perfluorononanoic acid, 6-phenylhexanoic acid and octyl phosphate; The first crystal form control agent is sugar and organic acid, and the total addition amount is 3-7% of the dry basis mass of calcium hydroxide.

4. The method for preparing the nano calcium carbonate with good high temperature resistance, flame retardancy and dispersibility according to claim 1, characterized in that: The second crystal form controlling agent described in step S1 is at least one of carborane derivatives, including o-carborane bisphenol, m-carborane bisphenol, 1-carboxy o-carborane, and 1,7-dicarboxylic acid m-carborane, and the added amount is 0.1-1% of the dry mass of calcium hydroxide.

5. The method for preparing the high temperature resistant and flame retardant nano calcium carbonate with good dispersibility according to claim 1, characterized in that: During the aging reaction described in step S2, CO2 gas is passed, or after the aging reaction is completed, CO2 gas is passed to make the pH <7.5 and the reaction is terminated.

6. The method for preparing the high temperature resistant, flame retardant and well dispersible nano calcium carbonate according to claim 1, characterized in that: The compounded surface modifier described in step S3 is a compound of sodium stearate and at least one of a phosphate containing a benzene ring structure or a phosphate containing a benzene ring structure, comprising the following steps: The sodium stearate saponification solution is added with a phosphate ester / phosphate solution containing a benzene ring structure, and the mixture is stirred evenly to obtain a composite surface modifier.

7. The method for preparing the high temperature resistant, flame retardant and well dispersible nano calcium carbonate according to claim 6, characterized in that: The phosphate containing a benzene ring structure includes any one of 4-methylumbelliferyl phosphate, S-binaphthol phosphate, R-binaphthol phosphate, 1-naphthyl phosphate, 2-naphthyl phosphate and bis(2,4-di-tert-butylphenyl) phosphate, and the content of the phosphate containing a benzene ring structure is 1-5% of the dry basis mass of calcium carbonate.

8. The method for preparing the high temperature resistant, flame retardant and well dispersible nano calcium carbonate according to claim 6, characterized in that: The phosphate containing a benzene ring structure includes any one of 4-methylumbelliferyl phosphate disodium salt, 1-naphthyl phosphate disodium salt and 2-naphthyl phosphate monosodium salt, and the content of the phosphate containing a benzene ring structure is 0.1-2% of the dry basis mass of calcium carbonate.

9. A nano calcium carbonate with high temperature resistance, flame retardancy and high dispersibility, characterized in that: The invention relates to nano calcium carbonate obtained by the preparation method according to any one of claims 1 to 17.

10. An application of the nano calcium carbonate with high temperature resistance, flame retardancy and high dispersibility as claimed in claim 9, characterized in that: Including use as fillers in plastics, rubber, coatings, and sealant products with high temperature resistance and flame retardant properties.